Heritage and urban planning in Lima: Bet and challenges for the diagnosis and proposal of Built Heritage into the PLAM 2035 - Ariza Fritas, Rosario (2018)
Built heritage is an essential and dynamic dimension of human activity. It encompasses privileges and challenges, qualitatively and quantitatively. The adequate management of this cultural heritage can mean an increase in quality of life for the communities of Lima. The analysis and proposal of built heritage management’s in Lima helps to develop a panoramical view and to organize pertinent data in a systematic way, much like “learned lessons”. This text explores the valuable and unique experience of developing the diagnosis and proposal of built heritage as a sectorial component and cross-horizon in the context of the Metropolitan Urban Development Plan of Lima (PLAM 2035). Recognizing the process of elaboration of this documentation will allow the assessment of its main force ideas and strategies to deal with the deficits and problems given rise by an environment with weak institutions and cultural citizenship, but also opportunities from the leadership of the Public Administration, specifically the City Government, to coordinate efforts and progress.